2022
DOI: 10.18820/2519593x/pie.v40.i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Technology inclusion for students living with disabilities through collaborative online learning during and beyond a pandemic

Abstract: Technology-based platforms in higher education institutions (HEIs), including online learning, require innovative approaches to ensure inclusive and transformative educational spaces for students living with disabilities. Achieving social equality, technology access and inclusion may contribute to ensuring a seamless instructional design for students living with disabilities in HEIs amid and beyond COVID-19. COVID-19 has obliged HEIs to adopt alternatives to learning and teaching, making the use of open distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
1
10
0
2
Order By: Relevance
“…Various article types were considered in this review, as shown in Table 2. Five of the twenty-one were theoretical or conceptual articles [8][9][10][11][12]. The majority of the articles, 13, were peer-reviewed research studies [13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Article Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…Various article types were considered in this review, as shown in Table 2. Five of the twenty-one were theoretical or conceptual articles [8][9][10][11][12]. The majority of the articles, 13, were peer-reviewed research studies [13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Article Typesmentioning
confidence: 99%
“…Of the twenty-one studies considered in this review, six were published in 2021 [11,16,21,26,27]. Thirteen articles were published in 2022 [8][9][10]14,15,17,18,20,[22][23][24][25]28]. Two articles reviewed were published in 2023 [12,13].…”
Section: Publications By Yearmentioning
confidence: 99%
“…Ante estos desafíos, sería conveniente una actualización y revisión del plan de estudios en los programas de formación docente, poniendo especial énfasis en la formación en T.A. para el alumnado NEAE, garantizando una distribución justa de recursos tecnológicos en todas las escuelas y fomentando la colaboración entre profesores, centros educativos y familias (De Klerk, 2022). Estas medidas no solo mejorarían la calidad de la educación, sino que también enriquecerían el ambiente en su totalidad, promoviendo prácticas inclusivas, como señalan Stenhoff et al (2020) y Steed et al (2022 en sus respectivos estudios.…”
Section: Interpretaciónunclassified
“…Teaching strategies in COIL environments are a way to provide collaborative and inclusive learning pathways. Klerk and Palmer (2022) provide a perspective with the application of COIL for students living with disabilities to transform their learning experiences and unlock new pathways for their development. In turn, Alvarez-Barreto et al (2022) constructed a COIL experience between Mexico and Ecuador where they supported project-based learning, with continuous evaluation of student satisfaction and skills developed, leading to increased engagement through greater social interaction and collaboration.…”
Section: Collaborative Online International Learningmentioning
confidence: 99%
“…Teaching strategies in COIL environments are a way to provide collaborative and inclusive learning pathways. Klerk and Palmer (2022) provide a perspective with the application of COIL for students living with disabilities to transform their learning experiences and unlock new pathways for their development. In turn, Álvarez-Barreto et al.…”
Section: Literature Reviewmentioning
confidence: 99%